Il borghese nel suo ambiente. Le radici del modernismo nella crisi del romanzo ottocentesco - Marangolo, Luca (Status Quaestionis, 2017)
This essay aims at analyzing the genealogical connection between modernism and the bourgeois novel of the XIX century. Modernism portrays itself traditionally in contrast with the bourgeois conservative tradition of its recent past: nevertheless, at the formal level, modernist innovations must be seen as a way to radicalize deep sociological contradictions of the bourgeois cultural system, which was dissolving across XIX and XX Century. From this perspective, some passages from two modernist masterpieces, Kafka’s Das Urteil (1912) and Virginia Woolf’s Mrs. Dalloway (1926), are here compared with late XIX novel, in order to conceptualize modernist form as way to react dialectically to a contradictory tradition with artistic innovation. Finally a basic hypothesis is put forward: the ultimate meaning of this modernist inner negotiation must be seen in the passage between late XIX century culture and the new XX mass culture; this transformation lies massively the way literature portraits the inner relation between the characters and their environment (Umwelt).